2022
DOI: 10.1111/cas.15329
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility study on collecting patient‐reported outcomes from breast cancer patients using the LINE‐ePRO system

Abstract: Due to the increasing complexity of cancer treatment, ensuring safety and maintaining the quality of life during treatment are important issues. Patient‐reported outcomes (PROs) in oncology are essential for assessing patient symptoms. A feasibility study was undertaken on breast cancer patients by building a PRO data collection system based on LINE, one of the most popular social network service applications in Japan. In this study, one or more predefined PRO questions for each breast cancer patient's clinica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…Remote monitoring by various professionals, such as nurses and pharmacists, facilitates a better understanding of the patient's condition and enables proactive interventions. Additionally, literature indicates that using LINE, a widely used social networking service in Japan, improved the response rate for e‐PRO 25 . The intervention method using e‐PRO is becoming diversified, and with the recent development of online medical consultations, it might be better to combine outpatient visits with online consultations to monitor the patient's condition while considering their burden and preferences.…”
Section: Discussionmentioning
confidence: 99%
“…Remote monitoring by various professionals, such as nurses and pharmacists, facilitates a better understanding of the patient's condition and enables proactive interventions. Additionally, literature indicates that using LINE, a widely used social networking service in Japan, improved the response rate for e‐PRO 25 . The intervention method using e‐PRO is becoming diversified, and with the recent development of online medical consultations, it might be better to combine outpatient visits with online consultations to monitor the patient's condition while considering their burden and preferences.…”
Section: Discussionmentioning
confidence: 99%
“…Previous PROM research has found that proactive PROMs, meaning that the clinicians actively review the patients' PRO answers during therapy and use the feedback from patients to optimise the treatment and care, 25 26 enable (1) earlier detection of symptoms; (2) improve communication between clinicians and patients about symptoms and HRQOL and (3) increase the personcentredness of consultation processes. [27][28][29][30][31][32] A personcentred approach focuses on the care and treatment of the needs of individuals and ensures that individual preferences, needs and values guide clinical decisions and that clinicians provide care that is respectful and responsive to patients. 33 Previous research in palliative care settings found that information on patients' perception of their state through PROMs may enable clinicians to enhance person-centred care and treatment if the perspectives and experiences of patients are revealed and integrated.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%
“…PROMs are defined as ‘any report of the status of a patient’s health condition that comes directly from the patient, without interpretation of the patient’s response by a clinician or anyone else’24 . Previous PROM research has found that proactive PROMs, meaning that the clinicians actively review the patients’ PRO answers during therapy and use the feedback from patients to optimise the treatment and care,25 26 enable (1) earlier detection of symptoms; (2) improve communication between clinicians and patients about symptoms and HRQOL and (3) increase the person-centredness of consultation processes 27–32. A person-centred approach focuses on the care and treatment of the needs of individuals and ensures that individual preferences, needs and values guide clinical decisions and that clinicians provide care that is respectful and responsive to patients 33.…”
Section: Introductionmentioning
confidence: 99%
“…Most studies and implementations of e-PRO systems have focused on specific diseases or conditions such as oncology. These systems have the potential to improve the identification and monitoring of essential aspects of care, such as treatment-related adverse effects (4)(5)(6)(7). These tools are growing in use and applicability and we believe that applying them to primary care and prevention could have myriad potential benefits (2,3,8).…”
Section: Introductionmentioning
confidence: 99%